Characterization of Cell Free Plasma Methyl-DNA From Xenografted Tumors to Guide the Selection of Diagnostic Markers for Early-Stage Cancers - Liu, Ling; Feng, Jinghua; Polimeni, Julian; Zhang, Manli; Nguyen, Hai; Das, Urmi; Zhang, Xu; Singh, Harminder; Yao, Xiao-Jian; Leygue, Etienne; Kung, Sam K. P.; Xie, Jiuyong (Frontiers in Oncology, 2021)
Circulating cell-free methyl-DNA (mcfDNA) contains promising cancer markers but its low abundance and possibly diverse origin pose challenges towards the accurate diagnosis of early stage cancers, for which using hundred thousands of markers together has given low success rates. By WGBS sequencing of cfDNA from about 0.5mL of plasma of mice xenografted with human tumours, we obtained the reads, aligned them to the human genome, filtered out the mouse and bacterial sequences, and confirmed the tumour origin of mcfDNA (mctDNA) by methylation-sensitive restriction enzyme digestion prior to species-specific PCR. We estimated human tumour-specific sequences to comprise about 0.29% of the xenograft mouse cfDNA or equivalent to about 0.026% human cfDNA. Similar WGBS of early stage (0-II, node- and metastasis-free) breast, lung and colorectal cancer samples identified hundreds of specific DMRs compared to healthy controls. Their association with tumourigenesis was supported by stage-dependent methylation, tumour suppressor or oncogene clusters, and genes also identified in the xenograft samples. Using 20 three-cancer-common and 17 colorectal cancerspecific DMRs in combination (top 0.0018% of the detected methylation clusters) was sufficient to distinguish the stage I colorectal cancers from breast and lung cancers and healthy controls. Our data thus confirmed the tumour origin of mctDNA by sequence specificity, and provide a selection threshold for authentic tumour mctDNA markers toward precise diagnosis of early stage cancers solely by top DMRs in combination.